2014
DOI: 10.1080/13854046.2014.911964
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Correlates of Functional Abilities in Individuals with Mild Cognitive Impairment: Comparison of Questionnaire, Direct Observation, and Performance-Based Measures

Abstract: The relationship between and the cognitive correlates of several proxy measures of functional status were studied in a population with mild cognitive impairment (MCI). Participants were 51 individuals diagnosed with MCI and 51 cognitively healthy older adults (OA). Participants completed performance-based functional status tests, standardized neuropsychological tests, and performed eight activities of daily living (e.g., watered plants, filled medication dispenser) while under direct observation in a campus ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 61 publications
4
45
1
Order By: Relevance
“…More specifically, poorer performances on tests of executive functioning (switching) and temporal order memory were related to poorer self-reported everyday functioning for the high SCC group. This pattern of findings is consistent with the literature, which suggests that memory and executive functioning, are related to everyday functioning in the older adult population and MCI populations (e.g., Farias et al, 2009; Jefferson, Paul, Ozonoff, & Cohen, 2006; McAlister, Schmitter-Edgecombe, & Lamb, 2016; Schmitter-Edgecombe & Parsey, 2014b). Further examination of the cognitive domains that may predict functional performance in individuals with SCC and their neural underpinnings may serve to refine the neuropsychological profile of SCC and development of sensitive cognitive tests.…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, poorer performances on tests of executive functioning (switching) and temporal order memory were related to poorer self-reported everyday functioning for the high SCC group. This pattern of findings is consistent with the literature, which suggests that memory and executive functioning, are related to everyday functioning in the older adult population and MCI populations (e.g., Farias et al, 2009; Jefferson, Paul, Ozonoff, & Cohen, 2006; McAlister, Schmitter-Edgecombe, & Lamb, 2016; Schmitter-Edgecombe & Parsey, 2014b). Further examination of the cognitive domains that may predict functional performance in individuals with SCC and their neural underpinnings may serve to refine the neuropsychological profile of SCC and development of sensitive cognitive tests.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the Alzheimer's Disease Cooperative Study/Activity of Daily Living Scale for individuals with MCI uses caregiver reports and can detect early changes in function between healthy controls and individuals with amnestic MCI (aMCI) . Qualitatively, the C‐IADL deficits found in that study are similar to those in the Rodakowski et al paper and include important activities such as shopping and checkbook balancing, and two other studies directly compared observed and reported C‐IADLs and showed a correlation between the two . On closer reading, Rodakowski et al.…”
supporting
confidence: 52%
“…Because this study was conducted as part of a larger study (Schmitter-Edgecombe et al, 2011), the OA control group represents a subsample of the 168 healthy older adults who best demographically matched the MCI and dementia participants. In addition, evaluation of the direct observation total accuracy score and cognitive correlates (no error analysis) was reported for a subset of the healthy older adults and individuals with MCI in a recent paper (Schmitter-Edgecombe & Parsey, in press). All older adult participants were given a report documenting their performance on the neuropsychological tests, as well as pre-paid parking passes, as compensation for their time.…”
Section: Methodsmentioning
confidence: 99%